Evaluasi kinerja manajemen risiko hukum dan risiko reputasi: Pendekatan self assessment di perbankan syariah - Lailiyah, Hasanatul (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the implementation of legal and reputation risk management at Bank SY. This research is a literature study research where data collection is obtained from various sources such as websites, books, and journals and uses descriptive analysis to describe the picture of the research study. The findings of this research, based on a self-assessment conducted by Bank SY, state that Bank SY has implemented 10 risk management well by obtaining a rating of 2 (low to medium) and obtaining a satisfactory predicate in the quality of risk management implementation. The ranking for the implementation of legal risk management itself is ranked 2 (low to medium), while the ranking for the implementation of reputation risk management is ranked 1 (low).